A METHOD FOR CLASSIFYING USABILITY FINDINGS TO ENHANCE VALIDATION OF NEW HEURISTICS - Salgado, André de Lima; Universidade de São Paulo (2019)
Different usability heuristics have been proposed as new application domains arise. Such proposals usually depend on the validation of the new heuristics. However, current validation methods are still biased by subjective comparisons of usability findings. In this paper, we aimed to enhance the process of matching usability finding descriptions and mitigate the bias of such process. To reach our goal, we adopted ontology techniques to extend the User Action Framework for the context of validating new usability heuristics. We tested three hypotheses about the feasibility of our new framework based on a case study with 173 usability findings. These usability findings were retrieved from an online project of a private mobile browser. Our data analysis of supported merging three classification schemes for our framework: User Action Framework, Typical Usability Defects (from ISO) and the heuristics of Nielsen. Finally, we describe a logical process for our method, because some of the contents from the classification schemes are not disjoint.